Interannual Variation in the Area and Water Volume of Lakes in Different Regions of the Tibet Plateau and Their Responses to Climate Change - Pang, Shuyu; Zhu, Liping; Yang, Ruimin (Frontiers in Earth Science, 2021)
The area and volume changes of 20 lakes that were present during the period 1976–2019 in different parts of the Tibet Plateau were extracted using Landsat remote sensing satellite images on the Google Earth Engine platform. Changes in the water volume of the lakes were analyzed using data from the digital elevation model. Basin scale interpolated meteorological data from the China regional surface meteorological feature dataset and the glacier distribution were used together with GIS technology and spatial statistical methods to reveal the impact of climate change and glacial melting water on the changes occurring in different regions. The results showed that both the area and water volume of the 20 studied lakes were generally stable from 1976–1986, increased significantly from 1986–1991, and decreased significantly from 1991–1995, after which they again began to increase. The increase in both amplitude and rate reached the highest values from 1995–2005, while the rate of increase slowed from 2014–2016. Precipitation and temperature are the main factors that result in the rapid increase of the water volume in closed lakes, but the influence of this phenomenon varies in different areas. The climate is relatively “warm and wet” around the inland enclosed lake areas in the southeast of the plateau where precipitation is the dominant factor and both precipitation and temperature affect the lake water volume in the center of the plateau; however, the climate is comparatively “cold and dry” in the northwest and the increase in glacier meltwater that results from increases in the temperature has a more significant impact.